A Derivative Spectrometric Method for Hydroquinone Determination in the Presence of Kojic Acid, Glycolic Acid, and Ascorbic Acid. (18th January 2017) - Moldovan, Zenovia; Popa, Dana Elena; David, Iulia Gabriela; Buleandra, Mihaela; Badea, Irinel Adriana
Abstract : A new, simple, and sensitive spectrometric method was developed for hydroquinone (HQ) determination in the presence of other depigmenting agents (kojic acid (KA), glycolic acid (GA), and ascorbic acid (AA)), commonly introduced in skin lightening products. The method is based on the oxidation of the depigmenting agents by potassium dichromate in sulfuric acid medium and subsequent measurement of the amplitude of the first-order derivative absorption spectrum at 268 nm. By applying the zero-crossing method, at this wavelength, the oxidation products of KA, AA, and GA do not interfere in the indirect determination of HQ. Beer's law was obeyed in the range of 0.22–22 μ g·mL −1 HQ, with a detection limit of 0.07 μ g·mL −1 . The developed method was applied with good results for the first time to the rapid determination of HQ in binary, ternary, and quaternary mixtures, thus proving that it could represent an effective tool for various skin lightening products analyses.